The use, integration and perceived value of performance analysis to professional and amateur Irish coaches - Martin, D.; Swanton, A.; Bradley, J.; McGrath, D. (International Journal of Sports Science & Coaching, 2018)
Research into the perceptions, practices and engagement of coaches with performance analysis is fundamental to informing the continued development of the discipline and its practitioners. The aim of this study was to survey a large sample of coaches of varying profiles, regarding their use and integration of performance analysis, to explore its perceived value and barriers to its use. Survey data were analysed from 538 Irish coaches qualified at Level 1 and above (82% male), from 37 sports. A spectrum of coaches` engagement with performance analysis, ranging from no formal performance analysis (49%), to coaches doing their own analysis (coach-as-analyst, 38%) and coaches with analyst-support (13%) was observed. The Level 2 coaching qualification was a key distinguisher between coaches using and not using performance analysis. Significant differences exist between the practices of coaches with and without analyst-support. Coaches with analyst-support are more likely to have regular access to video, spend more time analysing, regularly use performance analysis to inform training and use computerised analysis software. Barriers to the use of performance analysis varied along the spectrum of performance analysis engagement. This research can underpin future developments in coach and analyst education that will optimise the systematic use of PA across all levels of sports performance.